19 FETAL LUNG-TO-HEAD RATIO AND LIVER HERNIATION IN CONGENITAL DIAPHRAGMATIC HERNIA: PROGNOSTIC VALUE VARIES BASED ON SITE OF NEONATAL CARE. Issue 1 (1st January 2007) - Baraghoush, A.; Farrell, J.; Bisgaard, R.; Filly, R. A.; Lee, H.; Nobuhara, K. K.; Keller, R. L.
Abstract : Background: Congenital diaphragmatic hernia (CDH) causes fetal and neonatal lung hypoplasia. Severe fetal CDH has been defined by midgestation ultrasonography (US) and characterized by the presence of liver herniated into the thorax with a low lung-to-head ratio (LHR) (≤ 1.4). LHR is the area of the contralateral lung at the level of the cardiac atria divided by head circumference. We previously performed a single-center randomized study of fetal tracheal occlusion (FTO) versus standard care for severe fetal CDH. The trial was stopped prematurely due to an unexpectedly high survival rate in the control group (compared with historical data). Aim: To determine if survival to hospital discharge (DC) in infants receiving neonatal care at a single center (University of California, San Francisco [UCSF]) differs from survival at other centers (Other), after accounting for fetal liver herniation and LHR. Methods: We identified all UCSF US evaluations with diagnosis of CDH and LHR at 20 to 296/7 weeks' gestational age (GA, 1991-2006, n = 237). Patients were excluded if palliative care was elected ( n = 37) or survival was unknown ( n = 20). The primary outcome was survival to DC. If liver was herniated, fetal CDH severity was defined by LHR group (LHR ≤ 1.0 [LHR 1.0], 1.0 < LHR ≤ 1.4 [LHR 1-1.4], and LHR > 1.4 [LHR1.4]). Data were analyzed by chi square, Fisher's exact, or rank sum test; p < .05 was considered statistically significant. Results: Survival for infants with liver herniation and standard care at UCSF versus Other was 26 of 44 (59%) versus 40 of 82 (49%) ( p = .27). Evaluation by the LHR group revealed significantly better survival at UCSF in the lowest LHR group only (LHR 1.0: 17 of 30 [57%] vs 8 of 37 [22%], p = .003). In other LHR groups there were no significant survival differences (LHR 1-1.4: 6 of 8 [75%] vs 22 of 33 [67%], p = 1.0; LHR 1.4: 3 of 6 [50%] vs 10 of 12 [77%], p = .27). Without liver herniation, survival was not different by site of neonatal care (UCSF vs Other: 14 of 14 [100%] vs 12 of 16 [75%], p = .10). GA at delivery was comparable by site of care and CDH severity. There was no survival difference among UCSF infants with severe fetal CDH after FTO versus standard care (23 of 37 [62%] vs 23 of 38 [61%], p = .88). There were also no differences by LHR group. Conclusions: Survival differences based on fetal CDH severity were significantly different by site of neonatal care only for infants with the most severe fetal CDH (liver herniated, LHR 1.0). This difference may be explained by consistent care at UCSF, a high-volume neonatal referral center. There were no survival differences seen when evaluating only UCSF infants with severe fetal CDH, regardless of whether FTO was performed.